Digital health for remote home monitoring of patients with COVID-19 requiring oxygen: a cohort study and literature review - Chaytee, Johann; Dinh, Aurélien; D’Anglejan, Emma; Bouchand, Frédérique; Jaffal, Karim; Duran, Clara; Le Gall, Catherine (Frontiers in Medicine, 2024)
Background The clinical course and outcome of COVID-19 vary widely, from asymptomatic and mild to critical. Elderly patients and patients with comorbidities are at increased risk of respiratory failure and oxygen requirements. Due to the massive surge, the pandemic has created challenges for overwhelmed hospitals. Thus, the original home management of COVID-19 patients requiring oxygen and remote monitoring by a web app and a nurse at home were implemented in our center. We aimed to evaluate the outcome of patients with COVID-19 requiring oxygen who benefited from home remote monitoring management. Methods We performed a retrospective cohort study on all COVID-19 patients requiring oxygen (< 5 L/min) who consulted from October 2020 to April 2021 at our emergency department and were managed with home remote monitoring by a web app and an in-home nurse. We also carried out a literature review of studies on COVID-19 patients requiring oxygen with remote monitoring. Results We included 300 patients [184 (61.3%) male patients, median age 51 years]. The main comorbidities were cardiovascular disease (n = 117; 39.0%), diabetes mellitus (n = 72; 24.0%), and chronic respiratory disease (n = 32; 10.7%). Among the 28 (9.3%) patients readmitted to the hospital, 6 (1.9%) were hospitalized in the intensive care unit, and 3 (0.9%) died. In the multivariable analysis, risk factors for unplanned hospitalization were chronic respiratory failure (odds ratio (OR) =4.476, 95%CI 1.565–12.80), immunosuppression (OR = 3.736, 95%CI 1.208–11.552), and short delay between symptoms onset and start of telemonitoring (OR = 0.744, 95%CI 0.653–0.847). In the literature review, we identified seven other experiences of remote monitoring management. Mortality rate and unplanned hospitalization were low (maximum 1.9 and 12%, respectively). Conclusion Our study confirms the safety of home remote monitoring of patients with COVID-19 who require oxygen, as well as our literature review. However, patients with chronic respiratory failure and immunosuppression should be closely monitored.